Asenet se drievoudige transformasie. Vergelykende momente in die apokriewe verhaal "Josef en Asenet" en die Pauliniese corpus - J. A. du Rand (Acta Theologica)
Among theologians the apocryphal story of “Joseph and Aseneth” has in the majority of cases been interpreted as a narrative of transformation of Aseneth from a pagan to the Jewish religion of the God of Joseph. This one sided interpretation has dealt with the religious and cultural transformation but not with the gender transformation as such, namely the transformation of the woman from pagan reclusion, becoming a queen in her own right. Added to the religious and cultural transformation should be added the third transformation, the gender issue. This threefold transformation can be compared to the Pauline metaphor of “putting off” and “putting on” (of clothing) in Colosians 3:9-10. The primary concern in this passage is with a transformation of someone’s total being and outlook from the old to the new in a holistic way.